Bundle de cateter venoso central: conhecimento e comportamento dos profissionais de saúde da Unidade de Terapia Intensiva adulto de um hospital de grande porte - Camila Adriana Barbosa Costa (2017)
Primary bloodstream infections in a patient with a Central VenousCatheter (CVC) are among the frequently Health Care-Related Infections and can be associated to a longer hospitalization, higher morbidity and mortality, and the cost impacts in Adult Intensive Care Units (ICUs). Preventive measures such as having knowledge and the adoption of bundles by the health care team during the insertion and maintenance of CVC can reduce infections incidence. The hypothesis of this study is that the majority of health professionals working in an adult ICU, regardless of the category, are partially unknown and / or neglect the CVC infection prevention measures.OBJECTIVE: Evaluate the knowledge and behavior self-reported of professionals from an Adult Intensive Care Unit (ICU) of alarge hospital considering the recommendations of the bundle insertion and maintenance of the central venous access catheter. METHODOLOGY: Cross-sectional study carried out in an Adult Intensive Care Unit (ICU) of a large hospital in Belo Horizonte city, MG. Data collection was done in the form of face-to-face questionnaires, applied to 292 health professionals, among them physicians, nurses and nursing technicians, with questions elaborated according to recommendations for prevention of bloodstream infection by CVC described by the Centers for Disease Control and Prevention in 2011 and the National Sanitary Surveillance Agency in 2010. For the descriptive analysis of the qualitativevariables, it was used absolute and relative frequencies calculation, while for the descriptive analysis of the quantitative variables, central tendency and dispersion were used. To verify the comparison between the professional categories on the reasons attributed to central venouscatheter bloodstream infection, on the knowledge and behavior self-reported related to the CVC bundle, the Chi-square and Qui-Square Simulated tests were used for the qualitative variables. The Kruskal-Wallis test was used and when the test indicated a significantdifference the Nemenyi test was used for the multiple comparisons. For all analyzes of this work, software R version 3.3.1 was used. RESULTS: Regarding the 292 interviewed professional, most of them were women (77,74%) and with a median age of 32 years old. Among the professionals 61,30% were nursing technicians, 20,55% were physicians and 18,15% were nurses. As a contributing factor to CVC infection during insertion, 61,70% of the professionals attributed to a high time permanence of the catheter followed by absence and error in the technique of hand hygiene (surgical preparation) an error in the technique of hand and also of incorrect skins antisepsis technique, both with 58,51 %. Regarding maintenance, 97,95% of the respondents attributed to hands lack of hygiene before handling the device, and dont change the dressing when wet or with loosing edges (96,58%) as reasons for the occurrence of CVC infection; the lack of cleaning of the hub or connectors with alcohol at 70% was scored by 81.51% of professionals. Regarding the general knowledge about the CVC infection prevention bundle, more than a half of the interviewees (52,40%) reported to know bundle well, followed by moderate knowledge (40,75%). Among the items of knowledge self-reported, hands hygiene was the one with the highest agreement for insertion (92,46%) and also for maintenance (97,27%). The use of chlorhexidine degermante followed by alcoholic To prepare the skin (47,94%) and insert date on the hub /connectors (64,04%) were the ones with the lowest concordance. Regarding the behavior self-reported, 84,25% of the professionals reported always using the correct paramentation for insertion of the catheter, followed by hands hygiene (80,48%). When questioned about waiting for the effect of the antiseptic before inserting the CVC, 25,34% said they never proceeded with this recommendation and 23,86% never performed the cleaning of the hub /connectors with 70% alcohol. CONCLUSION: The professionals reported having good knowledge and appropriated behavior regarding some items, but not in the way the bundle predicts. Thus, the need for investments in training on this subject becomes evident. The evaluation of knowledge and behaviors favors the planning of interventions to improve the safety and quality of care provided to patients using CVC in the ICU.